Redefining the Envelope of Discrepancy in Contemporary Orthodontics: A Narrative Review - Shruti S. Biyani; Vinit D. Swami; Vasanthi V. Swami (Archives of Medicine and Health Sciences)
Redefining the envelope of discrepancy with temporary anchorage devices (TADs) refers to the use of mini-implants, miniplates, or miniscrews in orthodontics to expand the range of possible tooth movements and correct complex dental discrepancies. By strategically placing TADs in specific locations, orthodontists can create an augmented anchorage system that enables them to move teeth in ways that were previously not feasible. This expanded envelope of discrepancy allows for more efficient and effective treatment of complex malocclusions, including retraction of teeth, correction of severe crowding, open bites, deep bites, and cases with missing teeth. TADs allow orthodontists to have greater control over tooth movements, as they provide stable and reliable anchorage points. Orthodontists can tackle more challenging cases that were considered difficult or even impossible to treat. TADs minimize the dependence on patient cooperation since they provide additional anchorage independent of patient compliance. They can accelerate treatment by allowing orthodontists to move teeth more efficiently and effectively. Thus, treatment duration can be shortened, reducing the overall time patients spend in braces or aligners. Overall, redefining the envelope of discrepancy with TADs has significantly expanded the possibilities in orthodontic treatment, allowing for more precise and efficient correction of complex dental discrepancies.